Advertisement call of Brachycephalus albolineatus (Anura: Brachycephalidae) - Bornschein,Marcos R.; Ribeiro,Luiz Fernando; Rollo,Mario M.,Jr; Confetti,André E.; Pie,Marcio R. (PeerJ, 2018)
Background Brachycephalus are among the smallest terrestrial vertebrates in the world. The genus encompasses 34 species endemic to the Brazilian Atlantic Rainforest, occurring mostly in montane forests, with many species showing microendemic distributions to single mountaintops. It includes diurnal species living in the leaf litter and calling during the day, mainly during the warmer months of the year. The natural history of the vast majority of the species is unknown, such as their advertisement call, which has been described only for seven species of the genus. In the present study, we describe the advertisement call of Brachycephalus albolineatus, a recently described microendemic species from Santa Catarina, southern Brazil. Methods We analyzed 34 advertisement calls from 20 individuals of B. albolineatus, recorded between 5 and 6 February 2016 in the type locality of the species, Morro Boa Vista, on the border between the municipalities of Jaraguá do Sul and Massaranduba, Santa Catarina, southern Brazil. We collected five individuals as vouchers (they are from the type series of the species). We used the note-centered approach to describe the advertisement calls of the species. Results B. albolineatus have a long advertisement call of 40–191 s (mean of 88 s) composed of 8–29 notes (mean of 17 notes) emitted at a rate of 6–18 notes per minute (mean of 11 notes per minute) and at a note dominant frequency of five to seven kHz (mean of six kHz). Advertisement calls are composed of isolated notes and note groups (two notes involved in each particular note group); the former is composed by one to three pulses (mean of 2.0) and the note groups by two or three pulses in each note (mean of 2.7). Most advertisement calls present both isolated notes and note groups, with a few cases showing only the former. Note groups are emitted invariably in the last third of the advertisement call. Most isolated notes escalate their number of pulses along the advertisement call (1–2, 1–3 or 2–3). Note duration of isolated notes varies from 0.002 to 0.037 s (mean of 0.020 s) and duration of note group vary from 0.360 to 0.578 s (mean of 0.465 s). Discussion Individuals increase the complexity of their calls as they proceed, incorporating note groups and pulses per note. Intra-individual variation analysis also demonstrated that less structured advertisement calls (i.e., with notes with fewer pulses) are not stereotyped. It is possible that isolated notes and note groups could have distinct functions, perhaps territorial defense and mating, respectively. We argue that using a note-centered approach facilitates comparisons with calls of congeners, as well as underscores the considerable differences in call structure between species in a single group and among species groups.
Keywords: Bioacoustics; Note-centered approach; Brachycephalus albolineatus; Species groups; Call function